Sickle Mice Are Sensitive to Hypoxia/Ischemia-Induced Stroke but Respond to Tissue-Type Plasminogen Activator Treatment. Issue 12 (December 2017) - Sun, Yu-Yo; Lee, Jolly; Huang, Henry; Wagner, Mary B.; Joiner, Clinton H.; Archer, David R.; Kuan, Chia-Yi
Abstract : Background and Purpose—: The effects of lytic stroke therapy in patients with sickle cell anemia are unknown, although a recent study suggested that coexistent sickle cell anemia does not increase the risk of cerebral hemorrhage. This finding calls for systemic analysis of the effects of thrombolytic stroke therapy, first in humanized sickle mice, and then in patients. There is also a need for additional predictive markers of sickle cell anemia-associated vasculopathy. Methods—: We used Doppler ultrasound to examine the carotid artery of Townes sickle mice tested their responses to repetitive mild hypoxia–ischemia- and transient hypoxia–ischemia-induced stroke at 3 or 6 months of age, respectively. We also examined the effects of tPA (tissue-type plasminogen activator) treatment in transient hypoxia–ischemia-injured sickle mice. Results—: Three-month-old sickle cell (SS) mice showed elevated resistive index in the carotid artery and higher sensitivity to repetitive mild hypoxia–ischemia-induced cerebral infarct. Six-month-old SS mice showed greater resistive index and increased flow velocity without obstructive vasculopathy in the carotid artery. Instead, the cerebral vascular wall in SS mice showed ectopic expression of PAI-1 (plasminogen activator inhibitor-1) and P-selectin, suggesting a proadhesive and prothrombotic propensity. Indeed, SS mice showed enhanced leukocyte and platelet adherence to the cerebral vascular wall, broader fibrin deposition, and higher mortality after transient hypoxia–ischemia. Yet, post-transient hypoxia–ischemia treatment with tPA reduced thrombosis and mortality in SS mice. Conclusions—: Sickle mice are sensitive to hypoxia/ischemia-induced cerebral infarct but benefit from thrombolytic treatment. An increased resistive index in carotid arteries may be an early marker of sickle cell vasculopathy. Abstract : Supplemental Digital Content is available in the text.